Evaluating the Effectiveness of Zoning-Based Student Admission Policy: A Qualitative Study of Junior High Schools - Firdaus, Fadli (ETDC: Indonesian Journal of Research and Educational Review, 2025)
As a national policy, we introduced the zoning system to ensure equitable access to education and reduce the concentration of students in "favorite" schools. Despite efficient communication and sufficient administrative procedures, structural and social variables impede the policy's success. Therefore, this study aims to analyze the effectiveness of implementing the New Student Admission or PPDB zoning policy at public junior high schools. The research adopts a qualitative descriptive approach to explore the implementation process, focusing on four key variables based on Edward III’s policy implementation model: communication, resources, disposition, and bureaucratic structure. This research was conducted at public junior high schools in Sukabumi City, Indonesia. Data were collected through in-depth interviews, observations, and document analysis involving education officials, school administrators, local policymakers, and community representatives. Triangulation techniques were employed to validate the findings. The results show that Sukabumi has implemented the PPDB zoning policy in accordance with regulatory guidelines, yet several challenges persist. The uneven distribution of public schools across districts has created disparities in access, with some areas experiencing oversubscription and others lacking adequate school options. Additionally, limited digital literacy among parents and unequal school facilities have affected public acceptance of the policy. Despite effective communication efforts and adequate administrative procedures, the success of the policy is hindered by structural and social factors. In conclusion, the effectiveness of the zoning-based admission policy in Sukabumi depends not only on regulatory compliance but also on regional capacity and community support.